Biological properties of bovine immunoglobulins and systemic antibody responses - Musoke, A.J.; Rurangirwa, F.R.; Nantulya, V.M. (Cambridge University Press, 1986)
The classification of bovine immunoglobulins is similar to that of nonruminant mammals, namely IgM, IgA, IgG1, IgG2 and IgE. There are minimal differences between IgG1 and IgG2 in complement fixation, ability to mediate passive cutaneous anaphylaxis, phagocytosis of coated erythrocytes by cultured monocytes and precipitation of antigens bearing unique determinants, such as ovalbumin. The functional properties of bovine IgM are identical to those of the IgM of other mammals. The antigens used in elucidating these properties, however, were of noninfective origin. These studies were extended to infectious agents such as African trypanosomes and Theileria parva. Cattle infected with Trypanosoma congelense and T. brucei produced high levels of specific IgM and IgG antibodies that could inhibit infectivity and mediate phagocytosis of homologous trypanosomes. The IgM produced in T. brucei infections differed from that produced against noninfectious agents in that it induced adherence of sensitized trypanosomes to, and phagocytosis by, cultured bovine monocytes in the absence of heterologous complement. The ability of trypanosome-infected cattle to respond to superinfection was depressed depending on the time interval between the first and the second inoculations. Cattle vaccinated with Brucella abortus vaccine during acute or chronic infection with T. congelense or T. vivax also showed reduced responses to the vaccine. The nature of these altered responses was reminiscent of antigenic competition. Cattle responded to T. parva infections by producing antibodies to the three stages of the parasite, namely sporozoites, macroschizonts and piroplams. Only the anti-sporozoite antibodies could block entry of sporozoite antibodies could block entry of sporozoites into target cells.